A switchable dimeric yttrium complex and its three catalytic states in ring opening polymerization. Issue 8 (24th February 2021) - Deng, Shijie; Diaconescu, Paula L.
Abstract : A dimeric yttrium phenoxide complex can be oxidized in a stepwise fashion to access three oxidation states. The three states show different activity in the ring opening polymerization of cyclic esters and epoxides. Abstract : A dimeric yttrium phenoxide complex supported by a ferrocene Schiff base ligand, [(salfen)Y(OPh)]2 (salfen = ( N, N ′-bis(2, 4-di- tert -butylphenoxy)-1, 1′-ferrocenediimine), was synthesized and characterized. According to electrochemical studies and 1 H NMR spectroscopy, [(salfen)Y(OPh)]2 can be oxidized in a stepwise fashion to access three oxidation states. The catalytic activity of the three states toward the ring opening polymerization of cyclic esters and epoxides was investigated. The activity toward cyclic esters decreases upon oxidation while the opposite trend was observed in epoxide polymerization. Block copolymer syntheses using a redox switch were also performed.